Spacing-Switchable Multiwavelength Fiber Laser Based on Nonlinear Polarization Rotation and Brillouin Scattering in Photonic Crystal Fiber - Shahabuddin, N. S.; Ahmad, H.; Yusoff, Z.; Harun, S. W. (2012)
A new spacing-switchable multiwavelength erbium-doped fiber laser (EDFL) is demonstrated using switchable nonlinear polarization rotation (NPR) and stimulated Brillouin scattering (SBS) effects. The laser employs a 100-m-long photonic crystal fiber in conjunction with a four-port circulator in a figure-of-eight arrangement to provide the intensity-dependent transmission effect, as well as to discriminate the even-order and odd-order Brillouin Stokes to have a double-frequency Brillouin Stokes output. Without the Brillouin pump (BP), the laser operates in an NPR mode to produce at least 22 lasing wavelengths with a side mode suppression ratio of more than 10 dB and a wavelength spacing of 0.27 nm. In the Brillouin erbium fiber laser mode, at least 30 Brillouin lines with a spacing of 0.16 nm are obtained at BP power of 3 dBm and 980-nm pump power of 120 mW.